Pengaruh Interior Toko Oen Malang terhadap Perilaku Pengunjung - Sriti Mayang Sari, Cynthia Aprilita (Intra, 2014)
The interior design generally focuses on the aspect of function, but the development has a wider outreach, one of which is an aspect of human behavior as user space. The interior design is closely related to the problem of human activity, because people spend most of his life in a space. The major factor in the design of the interior is divided into three elements, human, space, and environment. This study aims to determine the effect of the interior of Toko Oen Malang visitor behavior, by using the theory of behavior settings. The results of this research indicate that the interior of Toko Oen Malang an impact on visitor activity pattern. It can be seen through the pattern of activity that is formed in each category, where visitors activity patterns are influenced by the shape, color, space organization, and circulation.